Learning Model Management for Slow Learners in an Inclusive Classroom Setting at an Elementary School - Iryana, Rina; Hidayat, Syarip; Mulyadi, Sima (Indonesian Journal of Primary Education, 2024)
The management of the slow learner learning model is a unique way of teaching and educating students who face challenges in comprehending the material to help them overcome hurdles and reach their full potential. This study aimed to determine the management of the learning model for children with special needs, particularly those who are slow learners, in an inclusive classroom setting at SDN Margaluyu, Tasikmalaya Regency. The research methodology employed in this study was a case study. The data collection methods employed included interviews, observations, and documentation analysis. This study's findings indicate no discernible differences in how teachers treated regular students and children with special needs throughout the initial phase of learning. This includes aspects such as their understanding of the subject matter, the methods used to educate, and the materials presented. However, there were notable disparities in the core learning activities, particularly in how the teacher facilitated student interaction. This included the way students asked questions of their peers and sought assistance from friends who were capable of teaching others. Additionally, students who were struggling with the material were not given the chance to ask the teacher directly, while instructions were provided to regular students to avoid discriminating against their peers. Throughout the entire duration of the core and closing activities, there was no variation in how the teacher treated the students. At the conclusion of each activity, the teacher provided positive feedback and reinforced it verbally by using phrases such as "good," "your answer is correct," and "excellent." Additionally, the teacher rewarded the students with stars, occasional bonus ratings, and applause. In conclusion, this study emphasizes the importance of effective collaboration between teachers and principals in designing service programs, infrastructure, and coaching to enhance students' potential, particularly those who are slow learners and face challenges in inclusive classrooms.